A decision support system for sustainable and resilient water-energy-food management - Sikka, Alok; Sena, Dipaka Ranjan; Alam, Mohammad Faiz; Behera, Abhijit; Chaudhary, Shivam; Sharma, Ruchi; Chandu, Navya (International Commission on Irrigation and Drainage (ICID), 2025)
The Water-Energy-Food (WEF) Nexus is increasingly recognized as a vital framework for addressing sustainability challenges, especially in regions facing growing pressure on natural resources and climate change. This paper introduces a Decision Support System (DSS) developed under the CGIAR Nexus Gains Initiative to support integrated WEF planning in India. The DSS integrates surface and groundwater models (SWAT+ and GWFLOW) with detailed land use and crop data to generate spatially explicit information on key hydrological and agricultural variables.